MATERI DAKWAH “LA MADDAREMMENG” DALAM MENGEMBANGKAN ISLAM DI KERAJAAN BONE PADA ABAD XVII - Hesti Andriani; Abd Rahim Yunus (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This research aims to describe what the results of the preaching carried out by La Maddaremmeng were like in the 17th century. The type of research used is library research. The research approaches used in this research are historical, sociological, political, and anthropological approaches. The data sources are primary and secondary. The data collection and processing methods consist of heuristics, interviews, documentation, source criticism, interpretation, and historiography. The results of this research show that the da'wah carried out by La Maddaremmeng in the 17th century was successful in instilling Islamic teachings in the people of Bone through planning da'wah materials, especially in aspects of the faith which had been adapted to the social conditions of the people who were the target of the da'wah. From the planning of the da'wah material, especially in aspects of the faith, it is then poured into the form of a da'wah method and the da'wah method that is practiced is the bil hal da'wah method, which then results in changes in the political, social, cultural and military fields. Apart from that, the next change was significant in religion, education, and architecture, Islam in the Kingdom of Bone. The conclusion above, implicitly shows that Islam in the Kingdom of Bone experienced very significant developments during the reign of King Bone La Maddaremmeng (1631-1644 AD). The implications of these changes had an impact on strengthening Islamic values as the official religion as well as becoming the basis for making policy